The Assessment of Scales of Frailty and Physical Performance Improves Prediction of Major Adverse Cardiac Events in Older Adults with Acute Coronary Syndrome. (10th May 2019) - Campo, Gianluca; Maietti, Elisa; Tonet, Elisabetta; Biscaglia, Simone; Ariza-Solè, Albert; Pavasini, Rita; Tebaldi, Matteo; Cimaglia, Paolo; Bugani, Giulia; Serenelli, Matteo; Ruggiero, Rossella; Vitali, Francesco; et al.
Abstract: Background: The number of older adults admitted to hospital for acute coronary syndrome (ACS) has increased worldwide. The aim of this study was to determine which scale of frailty or physical performance provides incremental improvements in risk stratification of older adults after ACS. Methods: A prospective cohort of 402 older (≥70 years) ACS patients were enrolled. Data about baseline characteristics, Global Registry of Acute Coronary Events (GRACE), and Thrombolysis in Myocardial Infarction (TIMI) risk scores were collected. Before hospital discharge, seven scales of frailty and physical performance were measured. The 1-year occurrence of adverse events (cardiac death, reinfarction, and cerebrovascular accident [MACCE] and all-cause mortality) was recorded. Results: Out of the 402 patients, 43 (10.5%) had a MACCE and 35 (8.7%) died. Following adjustment for confounding factors, scales of frailty and physical performance were associated with adverse events. Among the scales, the addition of short physical performance battery (SPPB) produced the highest incremental value over the initial model generated by baseline characteristics both for MACCE (ΔC-statistic 0.043, p = .04; integrated discrimination improvement (IDI) 0.054, p = .001; net reclassification improvement (NRI) 0.752, p < .001) and all-cause mortality (ΔC-statistic 0.063, p = .02; IDI 0.061, p < .001; NRI 1.022, p < .001). The addition of SPPB scale on top of GRACE or TIMI risk scores led to a considerable improvement in the prediction of MACCE and all-cause mortality (about 15% and 20%, respectively). Conclusions: The assessment of the physical performance with SPPB scale before hospital discharge increases the ability to predict adverse events in older ACS patients and may be useful in the clinical decision-making process. Clinical trial registration: www.clinicaltrials.gov NCT02386124.